2015
DOI: 10.1530/erc-15-0320
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic characterization of pituitary gigantism: an international collaborative study in 208 patients

Abstract: Despite being a classical growth disorder, pituitary gigantism has not been studied previously in a standardized way. We performed a retrospective, multicenter, international study to characterize a large series of pituitary gigantism patients. We included 208 patients (163 males; 78.4%) with growth hormone excess and a current/previous abnormal growth velocity for age or final height O2 S.D. above country normal means. The median onset of rapid growth was 13 years and occurred significantly earlier in females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
184
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(213 citation statements)
references
References 37 publications
8
184
1
7
Order By: Relevance
“…Hypopituitarism is reported in 64% of pituitary gigantism, the gonadal axis being most commonly affected [12], with delayed epiphyseal fusion increasing the time for growth, as in our patients. Epiphyseal fusion was successfully accelerated, with growth truncation in patient 1 who had an estimated final height of 240 cm, by using adult doses of testosterone for aromatization to oestrogen, plus a short course of oestrogen.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Hypopituitarism is reported in 64% of pituitary gigantism, the gonadal axis being most commonly affected [12], with delayed epiphyseal fusion increasing the time for growth, as in our patients. Epiphyseal fusion was successfully accelerated, with growth truncation in patient 1 who had an estimated final height of 240 cm, by using adult doses of testosterone for aromatization to oestrogen, plus a short course of oestrogen.…”
Section: Discussionsupporting
confidence: 59%
“…A 2011 a review of paediatric somatotropinomas reported 7 children, of whom 4 showed a clinical and biochemical response [11]. Combined pegvisomant with somatostatin analogues and dopamine agonists in pituitary gigantism has reported control in 53.5% cases [12], as seen in our case. Potential concern with pegvisomant includes the risk of tumour expansion, not seen in our patients.…”
Section: Discussionmentioning
confidence: 57%
“…Progressive macrocephaly has also been reported in children and may be the initial symptom, particularly during infancy [88]. Other features include coarsening of facial features, excessive sweating, and acral enlargement [89-91]. Although data is limited in children with GH excess regarding the risk of secondary malignances/cancer, studies in adults suggest that the overall cancer incidence in adults with acromegaly is not increased [92, 93].…”
Section: Growth Acceleration and Gh Excessmentioning
confidence: 99%
“…GH-secreting adenomas may be more aggressive and invasive than in adults [88, 94-97], have cosecretion of prolactin, and be associated with other pituitary hormone deficiencies in up to 25% of cases [91, 98-100], and they can be sporadic or associated with certain conditions including Carney complex, McCune Albright syndrome, MEN-1 syndrome, MEN-4 syndrome, and 3P association [101-104]. …”
Section: Growth Acceleration and Gh Excessmentioning
confidence: 99%
“…Patients with sporadic pituitary macroadenomas that occur during childhood/adolescence and early adulthood also should be considered to be at risk for an AIP mutation (12-20%). The young age at onset and the propensity for causing somatotropinomas means that AIP mutations are strongly associated with pituitary gigantism and represent the single most frequent genetic cause of pituitary gigantism [13]. The study by Ramírez-Rentería et al confirms that AIP mutations explain a small minority (7%) of sporadic acromegaly patients and that these patients exhibit aggressive features and an earlier age at onset than non-mutated cases.…”
mentioning
confidence: 94%